The birth and death of effectors in rapidly evolving filamentous pathogen genomes. (December 2018) - Fouché, Simone; Plissonneau, Clémence; Croll, Daniel
Highlights: Plant pathogens produce effectors to interfere with host defences and metabolism. Effector genes are among the most rapidly evolving genes in pathogen populations. Transcriptional control evolved in tandem with the chromosomal location of effectors. Chromosomal rearrangements are at the origin of high effector gain and loss rates. Abstract : Plant pathogenic fungi and oomycetes are major risks to food security due to their evolutionary success in overcoming plant defences. Pathogens produce effectors to interfere with host defences and metabolism. These effectors are often encoded in rapidly evolving compartments of the genome. We review how effector genes emerged and were lost in pathogen genomes drawing on the links between effector evolution and chromosomal rearrangements. Some new effectors entered pathogen genomes via horizontal transfer or introgression. However, new effector functions also arose through gene duplication or from previously non-coding sequences. The evolutionary success of an effector is tightly linked to its transcriptional regulation during host colonization. Some effectors converged on an epigenetic control of expression imposed by genomic defences against transposable elements. Transposable elements were also drivers of effector diversification and loss that led to mosaics in effector presence–absence variation. Such effector mosaics within species was the foundation for rapid pathogen adaptation.